2020
DOI: 10.15850/amj.v7n4.1916
|View full text |Cite
|
Sign up to set email alerts
|

Urine Color Analysis of Hydration Status in Employees Working in Bandung, Indonesia

Abstract: Background: Dehydration can be compensated for by the body. However, if it occurs persistently, it can cause concentration problems, thermoregulation disorders, kidney damage, and other life-threatening disorders such as cardiovascular disorders. Urine color is a simple indicator to assess a person’s hydration status. The purpose of this study was to explore the hydration status of employees working in Bandung, Indonesia. Methods: This was a descriptive cross-sectional study conducted from March to November 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…this results in changes in the kidney structure by a reduced size and number of the nephrons leading to decreased urinary output. This change starts slowly and progressively by age 20 years (Hauteas et al, 2020). On the other hand, Hooper et al (2016) contradicted with these results as they revealed that UC is too low to be helpful to discover hydration status in older people.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…this results in changes in the kidney structure by a reduced size and number of the nephrons leading to decreased urinary output. This change starts slowly and progressively by age 20 years (Hauteas et al, 2020). On the other hand, Hooper et al (2016) contradicted with these results as they revealed that UC is too low to be helpful to discover hydration status in older people.…”
Section: Discussionmentioning
confidence: 87%
“…In the present study, most of the patients had UC of dehydration. Hauteas et al (2020) showed that most of the studied patients suffered from severe dehydration based on evaluating their UC. Appearance of UC of dehydration indicates concentrated urine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation